1997
DOI: 10.1103/physrevb.55.4659
|View full text |Cite
|
Sign up to set email alerts
|

Local arrangement of silylene groups on Si(100)2×1 afterSiH4sdecomposition

Abstract: The interaction between Si͑100͒2ϫ1 and SiH 4 under UHV chemical vapor deposition conditions between 550 and 690 K is studied with high-resolution scanning tunneling microscopy and kinetic model calculations.In addition to small anisotropic Si islands and patches of hydrogen-terminated substrate, metastable crossshaped structural tetramer units are formed in this temperature region. These tetramers are interpreted as a combination of four SiH 2 groups connecting four Si substrate atoms, and their coverage is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Similar behaviors were reported by Bernasconi and Ceriotti 55, for the SiH 3 radical. Experimental works of Gates et al 74, Gates and Kulkarni 75, Bronikowski et al 76, and Spitzmuller et al 77, 78 show that highly hydrated adsorbed species as SiH 3 and SiH 2 have a brief lifetime on the surface and quickly decompose to the more stable monohydrate species. The enhanced reactivity of this adsorbed species was confirmed theoretically by Bernasconi and Ceriotti 55 and Lim et al 79, who calculated low energy barriers for both diffusion and decomposition of SiH 3 on the Si(100)2 × 1 surface.…”
Section: Elementary Processesmentioning
confidence: 99%
“…Similar behaviors were reported by Bernasconi and Ceriotti 55, for the SiH 3 radical. Experimental works of Gates et al 74, Gates and Kulkarni 75, Bronikowski et al 76, and Spitzmuller et al 77, 78 show that highly hydrated adsorbed species as SiH 3 and SiH 2 have a brief lifetime on the surface and quickly decompose to the more stable monohydrate species. The enhanced reactivity of this adsorbed species was confirmed theoretically by Bernasconi and Ceriotti 55 and Lim et al 79, who calculated low energy barriers for both diffusion and decomposition of SiH 3 on the Si(100)2 × 1 surface.…”
Section: Elementary Processesmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) studies have shown that island nucleation in SiH 4 -based ultrahigh vacuum CVD (UHV-CVD) on Si(100)-(2 × 1) depends very sensitively on the dissociation process of the SiH 4 molecule on the surface, since the kinetics of these coupled reactions determine the rate by which Si is supplied on the surface [5,6]. Additionally, surface diffusion is considerably hindered by the various hydrogen-containing species evolving on the surface from SiH 4 dissociation, which also influences island formation [7,8].…”
Section: And Sih 2 CL 2 At Intermediate Temperatures Is Illustratedmentioning
confidence: 99%